Spotlighting Plot Twists Within the Brevity of Flash Fiction - Novanda Lukwita Hakim; Happy Julia Rahmadianti; Nasywa Nuzula Ramadhani; Rindrah Kartiningsih; Rommel Utungga Pasopati; Anicleta Yuliastuti (AhInstitute of Research and Community Service (LP2M) Institute of Social Sciences and Business Andi Sapada, 2026)
This study examines how plot twists operate effectively within the constraints of flash fiction. Flash fiction, commonly defined as narratives under 1,000 words, has developed into a distinctive literary form characterized by extreme brevity and narrative economy. Despite its compressed structure, flash fiction can produce strong emotional and intellectual effects, often through the use of plot twists. These twists function as a crucial narrative strategy that subverts reader expectations and intensifies the impact of the story’s ending. In a genre where extensive characterization and detailed exposition are limited, plot twists become a central mechanism for creating narrative depth and maintaining reader engagement. The research aims to analyze narrative techniques that allow authors to construct impactful twists despite strict word limits. Using a qualitative textual analysis approach, the study analyzes selected flash fiction works that feature notable plot reversals. The analysis focuses on key narrative elements, including the structural placement of twists, foreshadowing, misdirection, and the strategic use of minimal detail. The findings indicate that successful plot twists in flash fiction depend on narrative compression, the manipulation of reader expectations, and the creation of cognitive surprise that encourages readers to reinterpret earlier elements of the story. In conclusion, it is proven that these strategies demonstrate how brevity can enhance, rather than limit, narrative complexity in micro-narratives.